GeoGebra Application Based Tutorial Materials to Improve Spatial Mathematics Abilities in Vocational High Schools - Edy Suprapto; Reza Kusuma Setyansah; Dea Devina (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
Spatial ability is crucial to solving mathematical problems. GeoGebra is one of the mathematics software systems widely used as an effective teaching media that is also reported to be effective to improve students’ spatial ability. This study aims to develop GeoGebra-based tutorial materials to increase students' mathematical spatial abilities at Vocational High Schools. This study involved 21 vocational high school students of the Accounting and Finance department. This study used the ADDIE Model (Analyze, Design, Develop, Implement, Evaluate). Research data were collected with a Pretest, a Posttest, students’ response questionnaires, and expert assessments. The findings proved an increase in students' mathematical spatial abilities after the use of GeoGebra-based tutorial material indicated by the validity assessed by two media experts and two material experts with a percentage of 90.13%, the practicality of the students’ limited test reaching a percentage of 83.24%, the effectiveness of the students’ learning completeness reaching a percentage of 82.22% and the practicality testing in the field trials reaching a percentage of 80.49%. The effectiveness of students’ learning completeness also achieved a percentage of 79.46%. The results of the gain normality test revealed that 19 students obtained high improvement and 2 students obtained low improvement. The total gain normality reached 0.9 indicating that the improvement was significant.